Bioequivalence study of two oral tablet formulations containing saquinavir mesylate boosted with ritonavir in healthy male subjects - Gustavo A, Yerino; Emilia K, Halabe; Elvira, Zini; Ethel C, Feleder (Arzneimittelforschung, 2011)
Saquinavir (SAQ) mesylate (CAS 149845-06-7) is a potent inhibitor of the HIV-1 protease indicated in combination with other antiretrovirals for the management of HIV-1 infection. The objective of this study was to compare rate and extent of absorption and to assess the bioequivalence between a new pharmaceutical equivalent tablet formulation containing 500 mg of SAQ mesylate and the innovator film coated tablet formulation. A randomized, single-center, open-label, twotreatment, two-sequence, three-period, replicated crossover bioequivalence study in 40 healthy male subjects was conducted. All subjects received 100 mg ritonavir (CAS 155213-67-5) twice daily for a run-in period of 3 days before treatment. Dosing was separated by a wash-out period of 14 days. Blood samples were collected over 72 h and plasma levels of SAQ were determined by a validated HPLC/UV assay. The 90%confidence interval(CI) of the ratio of the geometric means for logtransformed Cmax, AUClast and AUCinf values were used to assess bioequivalence using the equivalence interval of 80–125%. Point estimate and 90% CI of the ratios of Cmax, AUClast and AUCinf values were 94.9 (80.9–111.3), 97.4 (82.4–115.4) and 97.4 (82.5–115.0), respectively. Both treatments exhibited similar tolerability and safety. It was concluded that the new pharmaceutical product was bioequivalent to the innovator.
Keywords: Antiretroviral; Bioequivalence; Healthy volunteers; Saquinavir mesylate